2001
DOI: 10.21273/jashs.126.1.128
|View full text |Cite
|
Sign up to set email alerts
|

Shortwave Ultraviolet Irradiation for Control of Decay Caused by Botrytis cinerea in Bell Pepper: Induced Resistance and Germicidal Effects

Abstract: Shortwave ultraviolet radiation (UV-C) was tested for controlling natural infections and inducing resistance to fungal decay caused by Botrytis cinerea Pers.: Fr. (gray mold rot) in bell pepper [Capsicum annuum L. var. annuum (Grossum Group)] fruit. All UV-C doses tested (0.22, 0.44, 0.88, or 2.20 kJ·m-2) caused a reduction in the number of natural infections occurring during storage at 13 °C. A UV-C d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(48 citation statements)
references
References 18 publications
5
41
0
2
Order By: Relevance
“…Similar observations on the effectiveness of UV-C in reducing the microbial populations on food surfaces have been reported recently. UV-C with 2.2 and 4.4 kJ/m 2 intensity showed effectiveness in reducing the Botrytis cinerea population on bell peppers (Mercier, Baka, Reddy, Corcuff, & Arul, 2001). Syamaladevi et al (2014) reported 2.8 log reduction in P. expansum population on the pear surface after a UV-C dose of 1.7 kJ/m 2 .…”
Section: Resultsmentioning
confidence: 97%
“…Similar observations on the effectiveness of UV-C in reducing the microbial populations on food surfaces have been reported recently. UV-C with 2.2 and 4.4 kJ/m 2 intensity showed effectiveness in reducing the Botrytis cinerea population on bell peppers (Mercier, Baka, Reddy, Corcuff, & Arul, 2001). Syamaladevi et al (2014) reported 2.8 log reduction in P. expansum population on the pear surface after a UV-C dose of 1.7 kJ/m 2 .…”
Section: Resultsmentioning
confidence: 97%
“…The squarewave supplementation systems were used to provide desired UV-B radiation doses which were delivered from 0.5 m above the plant canopy for 8 h, each day, from 8:00 to 16:00 h by 8 fluorescent UV-B-313 lamps (Q-Panel Company, Cleveland, OH, USA) mounted horizontally on a metal frame inside each SPAR chamber. To filter-out and avoid the germicidal effects of UV-C radiation (<280 nm) (Mercier et al 2001), the lamps were wrapped with presolarized (kept under UV-B light for 48 h to stabilize transmission) 0.07 mm cellulose diacetate (CA) film (JCS Industries Inc., La Mirada, CA, USA). The CA film was changed every 3-4 d to account for the degradation of CA properties.…”
Section: Treatmentsmentioning
confidence: 99%
“…While artificial UV-C radiation also delays fruit ripening (Lu et al, 1991) and affects fruit softening (Ait Barka et al, 2000), literature on photochemical radiation with UV-C is primarily related to its germicidal activity and induction of disease resistance. The biological mechanisms by which such activity may take place include direct inactivation of conidia (Marquenie et al, 2002), elicitation of a wide array of compounds involved in defence responses, such as phytoalexins (Adrian et al, 2000;Ben-Yehoshua et al, 1992;Douillet-Breuil et al, 1999;Mercier et al, 1993Mercier et al, a, 1993Mercier et al, b, 2001, and accumulation of antifungal enzymes such as phenylalanine ammonia-lyase (Nigro et al, 1998(Nigro et al, , 2000, chitinase and β-1,3-glucanase (Porat et al, 1999). Many of these complex biochemical mechanisms involved in the induction of fruit resistance, such as preformed antifungals and pathogenesis-related proteins, are also elicited by heat treatments (Pavoncello et al, 2001).…”
Section: Firmnessmentioning
confidence: 99%
“…It has been reported that heat treatment and UV-C light could help to reduce fruit damage and pathogen attack during storage (Paull, 1990;Lurie, 1998;Baka et al, 1999;Marquenie et al, 2002Marquenie et al, , 2003. The beneficial effects of these treatments are thought to be mediated by different processes including inactivation of pathogens (Fallik et al, 1995), production of phytoalexins (Adrian et al, 2000;Ben-Yehoshua et al, 1992;Douillet-Breuil et al, 1999;Mercier et al, 1993aMercier et al, , 1993bMercier et al, , 2001, induction of defensive enzymes like phenylalanine ammonia-lyase (Nigro et al, 1998(Nigro et al, , 2000, peroxidases (Lurie et al, 1997), chitinases and glucanases (Schirra et al, 2000), and delayed cell-wall degradation (Lurie, 1998;Ait Barka et al, 2000;Paull and Chen, 2000).…”
Section: Combination Of Uv-c and Heat Treatments With Refrigerated Stmentioning
confidence: 99%